2018
DOI: 10.5334/labphon.93
|View full text |Cite
|
Sign up to set email alerts
|

What happens to large changes? Saltation produces well-liked outputs that are hard to generate

Abstract: Smolek, A. and Kapatsinski, V. 2018 What happens to large changes? Saltation produces well-liked outputs that are hard to generate. Laboratory Phonology: Journal of the Association for Laboratory Phonology 9(1): 10, pp. 1-27, DOI: https://doi.org/10.5334/labphon.93 lab l a phon . Recent research has argued that saltation is diachronically unstable and documented one possible cause of instability: Learners exposed to saltatory alternations may overgeneralize them to intermediate sounds. However, this research … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 53 publications
0
5
0
Order By: Relevance
“…As a result, the following dissociation can be predicted: a speaker can evaluate a form as being well-motivated, but be unable to produce it, to the extent that its production requires a second-order schema. This dissociation was observed by Smolek and Kapatsinski (2018) in a miniature artificial language learning study, which exposed participants to an articulatorily large typologically rare stem change (p→t ) unattested in the participants' native language (English). The participants rated plurals with the stem change as being more acceptable than those without (e.g., but i was rated to be a more likely plural form than bupi, given the singular bup).…”
Section: Coexistence Of Paradigmatic and Schematic Associationsmentioning
confidence: 93%
See 1 more Smart Citation
“…As a result, the following dissociation can be predicted: a speaker can evaluate a form as being well-motivated, but be unable to produce it, to the extent that its production requires a second-order schema. This dissociation was observed by Smolek and Kapatsinski (2018) in a miniature artificial language learning study, which exposed participants to an articulatorily large typologically rare stem change (p→t ) unattested in the participants' native language (English). The participants rated plurals with the stem change as being more acceptable than those without (e.g., but i was rated to be a more likely plural form than bupi, given the singular bup).…”
Section: Coexistence Of Paradigmatic and Schematic Associationsmentioning
confidence: 93%
“…Feedback is shown to help account for phenomena that otherwise require paradigmatic associations, limiting the range of situations in which paradigmatic associations must come into play. This is a desirable result because experimental studies show paradigmatic associations to be difficult to learn or apply (e.g., Braine et al, 1990 ; Smolek and Kapatsinski, 2018 ). On the methodological side, accepting this architecture changes what constitutes evidence for knowledge of a source-oriented, paradigmatic mapping.…”
Section: Introductionmentioning
confidence: 99%
“…The finding that learners in our study sometimes avoided using niwhen it triggered a phonological rule is consistent with the view that learners favor paradigm uniformity, meaning that they prefer morphemes to have the same phonological form across the contexts in which they appear (Hayes, 2004;Steriade, 2000). Paradigm uniformity effects have been found in a number of artificial language experiments with adults (Kapatsinski, 2009(Kapatsinski, , 2010(Kapatsinski, , 2013McMullin & Hansson, 2019;Smolek, 2019;Smolek & Kapatsinski, 2018;Stave et al, 2013;White, 2013White, , 2014 and children (Tessier, 2012). Much of the previous research on paradigm uniformity has focused on the application of a phonological rule itself, that is, whether a rule is under-applied (alternation avoidance) or over-applied (overgeneralization) in order to make members of a paradigm more similar to one another (see Smolek, 2019 for discussion of these two paradigm uniformity effects).…”
Section: Under-use Of the Rule-triggering Prefix Paradigm Uniformity ...mentioning
confidence: 99%
“…For example, the final /t/ phoneme of the verb stem pat becomes 'flapped' in American English when the -ing suffix is added (patting). Previous studies have suggested that phonological alternations are initially disfavored by learners, in artificial language learning experiments with adults and children (Kapatsinski, 2009;Smolek, 2019;Smolek & Kapatsinski, 2018;Stave, Smolek, & Kapatsinski, 2013;Tessier, 2012;White, 2013White, , 2014 as well as in children's natural language acquisition (Do, 2018;Kerkhoff, 2007). The second factor we consider is homophony avoidance.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation